Surgical and functional outcome of management of anterior column with posterior hemitransverse fracture of acetabulum - Chatrashali, Shivaraj A.; Patil, Alok C.; Nataraja, Chetan M.; Gaddi, Rakshith A. (International Journal of Research in Orthopaedics, 2024)
Fractures of acetabulum are relatively uncommon, but as they involve the major weight bearing joint in lower extremity, they assume great clinical importance. The displaced acetabular fracture fragments result in hip joint incongruity which in turn leads to abnormal pressure distribution over the articular cartilage surface. This may lead to accelerated breakdown of the articular cartilage, resulting in disabling irreversible arthritis of hip joint. The aim of treatment of these difficult acetabular fractures is concentric reduction of femur head under the weight bearing dome of acetabulum resulting in anatomic reduction and followed by a stable fixation. This can be achieved only by adequately exposing the acetabulum and by rigid internal fixation. In our series 20 patients were included. Majority of the patients were males with mean age of 43.85±16.88 years. Most common mechanism of injury was road traffic accident. Right side was most affected. Most of the cases were isolated injuries. Majority of the cases had no complications. At the final follow up, most of the cases had Excellent follow-up according to Modified Merle d’Aubigne and Postel score. Surgical management of Anterior column with posterior hemitransverse fracture of acetabulum gives excellent outcomes with least number of complications.